Case report: Undetected retained orbital wood fragment mimicking orbital cellulitis - Helen Katsarelis; Segun Awotesu; Tristan Mcmullan; Philip Ameerally (Elsevier, 2021)
Wooden foreign bodies (FBs) within the orbit are difficult to diagnose both clinically and radiologically [1]. In acute settings, wood can be missed on standard computerized tomography (CT) due to its hypodense appearance which can be mistaken for air. If left undetected, wood fragments impose a significant risk of infection [2]. Therefore, its prompt removal, particularly from the head and neck region, is essential.Our case describes a 31-year-old man who presented with a clinical picture of orbital cellulitis post trauma, who was later found to have a large retained fragment of wood, initially undetected on CT orbits.